EFFECTIVENESS OF VILLAGE FUND MANAGEMENT AND COMMUNITY EMPOWERMENT ASSISTANCE IN BULUNGAN DISTRICT - Imam Muazansyah; Irsyad Sudirman (DIA: Jurnal Administrasi Publik, 2022)
This study aims to determine the effectiveness of village fund management and community empowerment assistance in Bulungan Regency. This research uses a descriptive type of research with a qualitative approach or called descriptive qualitative in the form of research on the effectiveness of village fund management and assistance for improving community empowerment programs in Bulungan Regency using a naturalistic inquiry methodology with post-positivism. Data collection techniques in this research are library research, field studies in the form of observation, in-depth interviews, informants or research subjects, and documentation. Qualitative descriptive analysis was used in this study. The validity of this research data uses triangulation to check the validity of the data on the effectiveness of village fund management and community empowerment program assistance. This research is expected to provide recommendations and policies for the Bulungan Regency Government, especially the implementation of village fund management, as well as those related to village development and empowerment of rural communities so that they can develop independent villages. The expected output in this research is a mandatory scientific publication of an accredited National Journal. The Technology Readiness Level (TKT) proposed in this study is TKT 2 Types of Social Humanities.